(untitled) (Environment & Health, 2020)
Objective: We determined the collective effective and equivalent doses of the Ukrainian population and evaluated the radiation risks by the selected types of X-ray examinations. Materials and methods: The collective equivalent and effective doses of the population from the most widespread types of X-ray diagnostic examinations were calculated on the basis of the data of the national questionnaire of the research structure and the X-ray equipment park in Ukraine. The equivalent and effective doses of a “standard” patient at the X-ray exams were obtained from the results of the phantom modeling of the conditions of patient’s exposure and previous studies of the patients’ entrance surface doses. The absolute and relative radiation risks of the additional cancer cases in the Ukrainian population from X-ray diagnostic examinations were evaluated. Results and discussion: It has been established that during X-ray diagnostic studies on the old models of X-ray machines (analog systems), the effective doses of “standard” patients are 1.1–5.5 times higher than on modern devices with digital image receivers. This is due to the use of higher exposure values on analog devices. In recent years, there has been a tendency to decrease the absolute values of collective doses, which is associated with a decrease in the country’s population and a partial replacement of analog devices with digital imaging systems. The main contribution to the total collective effective dose of the population of Ukraine from the X-ray diagnostic examinations is provided by film fluorography – from 53.9 % in 2011 to 40.0% – in 2017, while the contribution of digital fluorography is 2.8 – 6.7% in the years of observation. The absolute expected risk due to the most common and dose-forming types of X-ray diagnostic examinations in the projection radiology is 1485 cases per year, the film fluorography makes the main contribution – 697 cases, while digital fluorography – 117 cases. Conclusion: The population’s collective effective dose in Ukraine due to the most common examinations in projection X-ray diagnostics was 22.9 thousand man-Sv in 2017, whereas in 2011 – 37.5 thousand people. The absolute risk of the additional cancer cases due to the selected types of X-ray diagnostic examinations is 1485.6 cases per year, while the contribution of film fluorography is 47%. The contribution of X-ray examinations to the increase in cancer incidence (attributive risk) made up 1.47%. The largest contribution is made by film fluorography – 0.95 % due to mass screening of lung diseases. Due to the fact that the attributive risk of film fluorography exceeds the acceptable risk, urgent measures are required to remove the film fluorography from radiological practice.